Reliability and accuracy of handheld stopwatches compared with electronic timing in measuring sprint performance - Hetzler, R. K.; Stickley, C. D.; Lundquist, K. M.; Kimura, I. F. (The Journal of Strength and Conditioning Research, 2008)
This study assessed reliability of split times obtained by handheld stopwatches (HHSs) compared with electronic timing (ET) during a 200-m sprint. Two HHS timing methods were compared with ET: single-split timers (SST) and multiple-split timers (MST). Twenty-six timers without previous experience were given instruction and completed practice trials until good agreement was achieved between ET and HHS. Trained runners (8 males, 10 females) were timed for each 25-m interval on a standard 200-m course. Repeated-measures analysis of variance and intraclass correlation models were used to determine reliability. A total of 248 split times were analyzed. No significant differences were found between the three timing methods (p > 0.99), and calculated intraclass correlation values were high (0.988). Mean error between SST, MST, and ET (-0.04 +/- 0.24 and -0.05 +/- 0.24 seconds, respectively) indicated faster HHS times, though not significantly. However, absolute errors were considerably larger (0.15 +/- 0.20 and 0.16 +/- 0.19 between SST, MST, and ET, respectively). The HHS-recorded splits were faster than ET in 67.3% of splits and slower in 29.4%. The distribution of errors made the development of a reliable correction factor to convert HHS to ET impossible. It was concluded that on the basis of the small mean error and high intraclass correlations, the use of HHSs may be a viable alternative to ET in collecting group data. However, on the basis of the absolute error between HHS and ET, when high degrees of precision are required, ET should be used, and reliable correction of HHS to ET values is not possible. It was further concluded that HHS times should be reported without attempting correction and interpreted in light of the shortcomings of the HHS method.